СУЧАСНИЙ УРОК В СИСТЕМІ ОСОБИСТІСНО ЗОРІЄНТОВАНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2002)
The article considers didactic features of the lesson in primary school with respect to personality-oriented education. The conditions providing effective education for each pupil as a personality are being analyzed.